1994
DOI: 10.1177/097133369400600202
|View full text |Cite
|
Sign up to set email alerts
|

Chinese and Australian Concepts of Intelligence

Abstract: The paper explores the Chinese conceptualisation of intelligence and points out how Western techniques of measurement of intellectual functions arefarfrom satisfactory. Two studies are presented. Both studies used the relevance rating technique to investigate the notion of intelligence held by two groups which differed in terms of culture and race (Australian and Taiwanese students, Study 1) and also in terms of educational experience (traditional Chinese and English schooling systems) but of the same culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…In conclusion, the present results support other studies which show that Chinese people emphasize Intelligent and Agreeable traits, 44,45 and also suggest that the four traits (Intelligent, Emotional, Unsocial and Agreeable) contribute to emotional symptoms differently in patients with bipolar I and II disorders. The present study, from a limited aspect, might offer culture-related clues to study emotional expression or control in Chinese people, to study the traitbases of the two types of bipolar disorder, and to develop bipolar type-specific psychotherapy strategies.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, the present results support other studies which show that Chinese people emphasize Intelligent and Agreeable traits, 44,45 and also suggest that the four traits (Intelligent, Emotional, Unsocial and Agreeable) contribute to emotional symptoms differently in patients with bipolar I and II disorders. The present study, from a limited aspect, might offer culture-related clues to study emotional expression or control in Chinese people, to study the traitbases of the two types of bipolar disorder, and to develop bipolar type-specific psychotherapy strategies.…”
Section: Discussionsupporting
confidence: 92%
“…That is, based on the 30 items used in the present questionnaire, there appeared to be little difference in the factor structures of the different groups. Assuming that these structures are accurate indicators of beliefs shaped by cultural environments, they provide evidence of cross-cultural similarity (at least in Malaysia, Britain and the US) in concepts about intelligence (Chen, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Yang and Sternberg (1997b) studied contemporary Taiwanese Chinese conceptions of intelligence, and found five factors underlying these conceptions: (a) a general cognitive factor, much like the g factor in conventional Western tests; (b) interpersonal intelligence (i.e., social competence); (c) intrapersonal intelligence; (d) intellectual self-assertion; and (e) intellectual self-effacement. In a related study but with different results, Chen (1994) found three factors underlying Chinese conceptualizations of intelligence: nonverbal reasoning ability, verbal reasoning ability, and rote memory. The difference may be due to different subpopulations of Chinese, to differences in methodology, or to differences in when the studies were done.…”
Section: Implicit Theories Of Intelligence Across Culturesmentioning
confidence: 94%
“…Of course, comparing the Chen (1994) to the Sternberg et al (1981) study simultaneously varies both language and culture.…”
Section: Implicit Theories Of Intelligence Across Culturesmentioning
confidence: 99%